Réponses

2014-04-27T19:24:23+02:00
G= (x - 5)² - (x - 5) (7 - 2x)
G= x² - 10x + 25 - (7x - 2x² - 35 + 10x)
G= x² - 10x + 25 - (-2x² + 17x - 35)
G= 3x² - 27x + 60 

G= (x - 5)² - (x - 5) (7 - 2x)
G= (x - 5) (x - 5 - 7 + 2x)
G= (x - 5) (3x - 12)

G= (x - 5)² - (x - 5) (7 - 2x)
G= (-3 - 5)² - (-3 - 5) (7 - 2 * (-3))
G= 9 + 25 - (-8) (7 - 6)
G= 34 - (-8)
G= 34 + 8
G= 42

(x - 5) (3x - 12) = 0
x - 5 = 0 OU 3x - 12 = 0
x = 5 OU 3x = 12
x = 5 OU 3x/3 = 12/3 
x = 5 OU x = 4 

Les solutions de l'équation sont x = 5 et x = 4. 

Voilàa !